The effect of source and maturity on the stable isotopic compositions of individual hydrocarbons in sediments and crude oils from the Vulcan Sub-basin, Timor Sea, Northern Australia - Dawson, Daniel; Grice, Kliti; Alexander, Robert; Edwards, D. (Elsevier Science, 2007)
Recent work has demonstrated the effect of maturation on the stable hydrogen isotopic compositions (delta D) of individual sedimentary hydrocarbons (n-alkanes, pristane and phytane) in a series of marine source rocks from the Perth Basin (Western Australia). There was an enrichment in deuterium (D) in the hydrocarbons with increasing maturity, attributed to isotopic exchange associated with thermal maturation. An initial, large (P approximate to 115 parts per thousand.,) biologically derived difference between the delta D values of n-alkanes and isoprenoids gradually decreased as pristane and phytane became enriched in D, while the n-alkanes generally remained at constant isotopic composition. This work has now been extended to include a series of Late Jurassic sediments from the lower Vulcan Formation of the Vulcan Sub-basin (Timor Sea, Northern Australia), where the delta D values of n-alkanes and isoprenoids show similar trends to those observed for the Perth Basin. The enrichment in D in isoprenoids correlates strongly with traditional maturity parameters and is shown to be related to the epimerisation of pristane and phytane. Pristane and phytane extracted from a post-mature Paqualin-1 sediment are significantly enriched in D relative to the n-alkanes, indicating that D enrichment persists at very high maturity, more so for regular isoprenoids than n-alkanes. This supports the notion that hydrogen (H/D) exchange causes the observed shift in delta D values, and not free radical hydrogen transfer. A mechanism is proposed which can account for both H/D exchange and epimerisation of pristane and phytane in the sedimentary environment. Pristane is enriched in D relative to phytane throughout the Vulcan Sub-basin sequences, attributed to a lower relative algal input to the isoprenoids, and indicating that they exchange hydrogen at similar rates during maturation. Crude oils and condensates from the sub-basin were also analysed to evaluate their source and thermal maturity and the results complement previous molecular and stable carbon isotopic analysis. The delta D values of n-alkanes and regular isoprenoids largely support the previous classification of Vulcan Sub-basin crude oils and condensates into two groups: Group A, having a marine source affinity and Group B, a terrigenous source affinity. Some oils and condensates are suggested to be a mixture of sources A and B, or A and other as yet unknown sources. Tenacious-1 crude oil (formerly a Group A oil) contains n-alkanes with more positive delta D values than other Group A oils and is suggested to have been mixed with another source of more mature hydrocarbons. The Group A crude oils and condensates show an upward inflection in the n-alkane delta D profile from n-C-11 to n-C-15, which is suggested to represent an addition of D-enriched lower molecular weight n-alkanes from a more mature wet gas/condensate to an initial oil charge. The small differences between the delta D values of the n-alkanes and regular isoprenoids in the crude oils and condensates indicate that significant H/D exchange has taken place, implying that the samples were generated from mature source rocks.